PENGARUH PENGETAHUAN PERPAJAKAN DAN KUALITAS PELAYANAN PAJAK TERHADAP MOTIVASI DALAM MEMBAYAR PAJAK PENGHASILAN (STUDI PADA WPOP DI KEC. WANEA KOTA MANADO) - Cimberly, Polii; Manossoh, Hendrik; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
This research aims to examine the effect of tax knowledge and the quality of tax service on motivation in paying income tax. The sample in this research are all individual taxpayers who reside in the district wanea of manado city. The data in this research is using primary data. It was collected by distributing questionnaires directly to individual taxpayers in the district wanea of manado city. The data taken was processed using the multiple linear regression analysis with the help ofÂ  SPSS 23. The result indicate that: tax knowledge has positive effect towards motivation in paying income tax. The quality of tax service has positive effect towards motivation in paying income tax. Tax knowledge and the quality of tax service simultaneously have positive effect towards motivation in paying income tax.Keywords: Tax Knowledge, The Quality of Tax Service, Motivation In Paying Income Tax.